Digital Parenting Strategies And Their Effectiveness In Setting Limits On Gadget Use In Children Early Childhood In Central Java Province - Asri Arofah As'adati Mustaghfiroh; Adi Wibowo; Yazid Al Ansori (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The free use of gadgets without clear boundaries from parents can cause psychological problems in children, causing addiction, difficulty concentrating on learning activities, irritability when prohibited, and lack of social interaction with peers. In addition, language and motor development can also be hampered because children are more passive. In addition, it causes speech delays and visual impairments in children and their rest time is disrupted. Even the content is not age-appropriate . Without guidance, children can be influenced, causing difficulty concentrating . Therefore, guidance and clear boundaries from adults, especially parents, are needed at home.